FM-CATH, A Novel Cathelicidin From Fejervarya Multistriata, Shows Therapeutic Potential for Treatment of CLP-Induced Sepsis - Wu, Jiena; Zhang, Haiyun; Chen, Xiaoxin; Chai, Jinwei; Hu, Yunrui; Xiong, Weichen; Lu, Wancheng; Tian, Maolin; Chen, Xin; Xu, Xueqing (Frontiers in Pharmacology, 2021)
Sepsis is an exacerbated inflammatory reaction induced by severe infection. As important defensive molecules in innate immunity, several AMPs are reported to prevent septic shock. In this study, we characterized a novel cathelicidin, FM-CATH, from the frog skin of Fejervarya multistriata. FM-CATH was found to adopt an amphipathic α-helix structural in membrane-mimetic environments and possess favorable antimicrobial effects against bacteria and fungus. In addition, it triggered the agglutination of bacteria. It could also strongly bind to LPS and LTA. Additionally, FM-CATH affected the enzymatic activities of thrombin, plasmin, β-tryptase, and tPA, leading to coagulation inhibition in vitro and in vivo. Finally, we observed that FM-CATH improved survival rate and inhibited pathological alteration, bacterial count, serum biochemistry, and pro-inflammatory cytokine expression in the cecal ligation and puncture-induced sepsis mice. Taken together, these findings suggest that FM-CATH might be served as a promising agent for the treatment of sepsis.